THE RISK FACTOR DIABETES MELLITUS FOR WOMEN IN SAYUR MATINGGI LOCAL COMMUNITY HEALTH CENTER OF TAPANULI SELATAN YEAR 2017 - RAISAH DEWI; UMAR ZEIN; RAZIA BEGUM SUROYO (LP2MTBM MAKARIOZ, 2020)
Diabetes Mellitus is disease already from the last and now always in crease, in a now time thriue, it is in village it is in town. Diabetes mellitus in desease that happen result of problemon pancreas has not to produce insulin with our body. The purpose of research as for analysis factor of risk that there is relation with diabetes mellitus for womwn in Sayur Matinggi year 2017. The type of research is use analytic survey with case control desain population for case is the peoples suffer diabetes mellitus community health center of Tapanuli Selatan year 2017. Sample for this research are 68 peoples for case and 68 peoples for control with systematic random sampling technique. The result of the bivariate analysis uses chi square test, it show of the risk factors about diabetes mellitus are family history ( OR= 2,79), diatery habit table (OR= 3,26), physical actity ( OR= 5,46), body mass index ( OR= 2,35). By statistic tes has know that from chi square test has result of family history sig- p ( 0,006 ), diater habbit ( 0,002 ), physical acticity ( 0,000 ), body mass index sig- p (0,024 ), smaller from sig- a ( 0,005 ) and so that Ho rejected, and than it has conclude, there is relationship between family history, diatery habit, physical activity and body mass index with the incidence of diabetes mellitus. From the between risk factors incidence of diabetes mellitus. Physical activity has relationship with incidence of diabetes mellitus that highest is light physical activity with odd ratio = 5,46 it shows to respondents with light physical activity five times tend to suffer from diabetes mellitus. Be expect to all of healthy workers to give health promotion about knowledge of diabetes mellitus, so that it can lower and prevent incidence of diabetes mellitus.